It's classified: Classification, disability rights and Commonwealth Games - Quinn, Nancy; Misener, Laura (Frontiers in Sports and Active Living, 2023)
Sport events are often held up as opportunities to showcase excellence and further access to opportunities for sport participation. The ethos of accessibility has come to the forefront of many events, but none more so than the Commonwealth Games (CG). CG uses the ethos of inclusivity to bring the Commonwealth (CW) community together and utilizes sport to celebrate, uphold and drive its vision and values: Humanity, Destiny, Equality (CGF, 2022). However there remain significant gaps in participation opportunities and the realization of equality through CG, particularly for lower resource CW nations. CG is also the only global multisport event that integrates athletes with disabilities (para sport athletes), and yet there persist significant constraints to the creation of equitable opportunities for full participation for many para sport athletes. Shalala (2022) wrote “How can you effectively achieve integration (during CG), while ensuring the gulf between the best and the rest doesn't become a seismic divide?” We echo Shalala’s concerns. Through this review we intend to examine sport classification as exemplary of the opportunities and hindrances for CG to actualize their values of ‘equality, humanity and destiny’ for para sport and athletes, specifically from developing CW nations, and guard against the growing chasm “between the best and the rest”. Of significance, we consider, through a human rights lens, the impact of sport classification on the integration of para sport and athletes at CGs, and the future of Commonwealth-wide participation and the integrated model itself.